Pengaruh Stres Kerja dan Lingkungan Kerja terhadap Kinerja Pegawai di Dinas Lingkungan Hidup Kabupaten Purbalingga - Aditya, Fajar Robi; Barima, Hima; Supriatin, Dyah (UNPERBA, 2023)
Based on performance appraisal data at the Purbalingga Regency Environmental Service, namely in 2020 and 2021 performance has decreased, from the results of pre-research the phenomenon that occurs is work stress, namely role demands and task demands, where the lack of experts makes employees have to perform tasks beyond their capabilities , while the phenomenon in the work environment is that the work space is less spacious, the wall coloring is not quite right, the lack of facilities in the meeting room. The type of research used is quantitative. The population in this study were all employees with a total sample of 95 people. The data collection technique used was a questionnaire using multiple linear regression analysis with SPSS 20. The results showed that partially the Job Stress variable had a negative and significant effect on performance and the Work Environment partially had a significant positive effect on employee performance. In addition, the variables of Work Stress and Work Environment simultaneously have a significant effect on employee performance which can be seen from the calculated F value of 11.585 while the Ftable value is 3.10, so it can be concluded that the Employee Performance variable (Y) can be significantly influenced by the independent variables work stress (X1) and work environment (X2). The coefficient of determination (R-Square) is 0.201. This means that 79.% of the employee performance variable will be influenced by other variables not discussed in this study.